Variability of tissue factor‐activated thromboelastography and whole blood impedance platelet aggregometry in healthy dogs. Issue 4 (19th June 2018) - Shropshire, Sarah B.; Olver, Christine S.; Lappin, Michael R.
Abstract: Objective: To assess interindividual (CVG ) and intraindividual (CVI ) variability over time for results of thromboelastography (TEG) and whole‐blood impedance platelet aggregometry in healthy dogs. Animals: Six healthy Beagle dogs. Measurements and Main Results: Tissue factor (TF)‐activated TEG and adenosine diphosphate (ADP) and arachidonic acid (AA)‐induced whole blood impedance platelet aggregometry were performed at 3 different time points (days 1, 4, and 6). In addition, platelet count, hematocrit, and plasma fibrinogen concentrations were recorded each study day. Activated partial thromboplastin time, one‐stage prothrombin time, antithrombin activity, and D‐dimer concentrations were measured on the first day of the study. For TEG, the variables reaction time ( R ), clotting time ( K ), rate of clot formation ( α ), and maximum amplitude (MA) were recorded. For platelet aggregometry, the areas under the curve for ADP (AUCADP )‐ and AA (AUCAA )‐induced aggregation were measured. The CVI was lower than the CVG over time for MA, AUCADP, and AUCAA ; however, the CVI was higher than the CVG for the TEG variables R, K, and α . There were no statistical differences in the platelet count, hematocrit, and fibrinogen measurements over time. Conclusions: In healthy dogs, a subject‐based reference interval for ADP‐ and AA‐induced platelet aggregometry and the TEG variable MA provide a more sensitive method to detect changes. However, due to the high CVI, population‐based reference intervals may be more appropriate for interpretation of the TEG variables R, K, and α .